2016
DOI: 10.1074/jbc.m115.691113
|View full text |Cite
|
Sign up to set email alerts
|

Low pH and Anionic Lipid-dependent Fusion of Uukuniemi Phlebovirus to Liposomes

Abstract: Many phleboviruses (family Bunyaviridae) are emerging as medically important viruses. These viruses enter target cells by endocytosis and low pH-dependent membrane fusion in late endosomes. However, the necessary and sufficient factors for fusion have not been fully characterized. We have studied the minimal fusion requirements of a prototypic phlebovirus, Uukuniemi virus, in an in vitro virus-liposome assay. We show that efficient lipid mixing between viral and liposome membranes requires close to physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 60 publications
8
59
0
Order By: Relevance
“…Depending on the virus, this activation can occur in the slightly acidic environment of the early endosomes, for instance for the nairovirus CCHFV or for Lacrosse virus (LACV, an orthobunyavirus), which are activated at pH 6.0 (Garrison et al, 2013;Plassmeyer et al, 2007) or in the more acidic late endosomes, like the UUKV phlebovirus, which is activated at pH 5.4 (Lozach et al, 2010), or the RVFV phlebovirus, which is activated at pH 5.7 (de Boer et al, 2012). In addition to pH, other factors are important to trigger the membrane fusion reaction: proteolytic cleavage of the glycoproteins for nairoviruses (Sanchez et al, 2002) or the presence of specific lipids in the cellular membrane, like cholesterol in hantaviruses (Kleinfelter et al, 2015) or anionic lipids as bis(monoacylglycero)phosphate or phosphatidylglycerol (PG) in the tick-borne UUKV phlebovirus (Bitto et al, 2016).…”
Section: Bunyavirus Entry Into Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the virus, this activation can occur in the slightly acidic environment of the early endosomes, for instance for the nairovirus CCHFV or for Lacrosse virus (LACV, an orthobunyavirus), which are activated at pH 6.0 (Garrison et al, 2013;Plassmeyer et al, 2007) or in the more acidic late endosomes, like the UUKV phlebovirus, which is activated at pH 5.4 (Lozach et al, 2010), or the RVFV phlebovirus, which is activated at pH 5.7 (de Boer et al, 2012). In addition to pH, other factors are important to trigger the membrane fusion reaction: proteolytic cleavage of the glycoproteins for nairoviruses (Sanchez et al, 2002) or the presence of specific lipids in the cellular membrane, like cholesterol in hantaviruses (Kleinfelter et al, 2015) or anionic lipids as bis(monoacylglycero)phosphate or phosphatidylglycerol (PG) in the tick-borne UUKV phlebovirus (Bitto et al, 2016).…”
Section: Bunyavirus Entry Into Cellsmentioning
confidence: 99%
“…Similarly, disruption of the membrane-bound host enzyme S1P (for "transcription factor peptidase/site-1"), which causes a modest cholesterol depletion in target cells, led to an important reduction of infectivity levels by Hantaan virus and by Andes virus in haploid human (HAP1) cells (Kleinfelter et al, 2015;Petersen et al, 2014), reflecting the importance of high cholesterol levels for hGc insertion to target membranes. For phleboviruses, cholesterol was shown to play a role in viral entry for the mosquito-borne RVFV (Harmon et al, 2012), but not for the tickborne UUKV, for which the membrane fusion reaction requires the presence of anionic lipids in the target membrane, but not cholesterol (Bitto et al, 2016). For nairoviruses, cholesterol depletion significantly inhibited CCHFV infection, and the infection levels can be recovered after the addition of exogenous cholesterol (Simon et al, 2009).…”
Section: Lipid Sensingmentioning
confidence: 99%
“…Indeed, several experiments have indicated that class II fusion glycoproteins are monomeric when they interact with the target membrane [66]. Cryoelectron tomography (cryo-ET) analysis revealed bridge-like densities between acidified virions and liposomes with dimensions consistent with those of extended monomers for Rift Valley fever virus [67], Uukuniemi virus (another phlebovirus) [68] and Sindbis virus (an alphavirus) [69]. In the latter case, the orientation of the fusion glycoprotein (E1) relative to the virus surface appeared to be variable.…”
Section: Differences and Similarities With Other Viral Fusion Glycoprmentioning
confidence: 99%
“…A pH dependency of endocytotic processes has been described almost exclusively for the entry of viruses into cells. 34,35 In this study, the phenomenon was mostly attributed to changes in the charge of the virus particles, which allows fusion with the cell membrane. 34 However, since, in the current study, only uncharged dextran has been used for the analysis of macropinocytosis, this mechanism cannot explain the observed pH dependency.…”
mentioning
confidence: 99%